The Emergence of Primary Anoetic Consciousness in Episodic Memory - Vandekerckhove, Marie; Bulnes, Luis Carlo; Panksepp, Jaak (Frontiers in Behavioral Neuroscience, 2014)
Based on an interdisciplinary perspective, we discuss how primary-process, anoetic forms of consciousness emerge into higher forms of awareness such as knowledge-based episodic knowing or noetic consciousness and self-aware forms of higher-order consciousness like autonoetic awareness. Anoetic consciousness is defined as the rudimentary state of raw affective, homeostatic and sensory-perceptual mental experiences. It can be considered as the autonomic flow of primary-process phenomenal experiences that reflect a fundamental form of first-person “self-experience,” a vastly underestimated primary form of consciousness. We argue that this anoetic form of consciousness constitutes an antecedent that is foundational for all forms of knowledge acquisition via learning and memory as well as higher forms of “awareness” or “knowing consciousness”. We summarize the conceptual advantages of such a multi-tiered neuroevolutionary approach to psychological issues, namely from genetically controlled primary (instinctual) and secondary (learning and memory), to higher tertiary (developmentally emergent) brainmind processes, along with suggestions about how affective experiences becomes more cognitive and object-oriented, allowing the developmental creation of more subtle higher mental processes such as episodic memory which allows the possibility of autonoetic consciousness, namely looking forward and backward at one’s life with the “mind’s eye”.